The Saint and the Madman: Antonin Artaud and the Mystical Experience in Madness - Visser, Joeri (Studies in spirituality, 2025)
This article investigates the writings of Antonin Artaud (1896-1948) from the time he was interned in the psychiatric hospital of Rodez. From a mystical point of view, we will see how Artaud’s mystical experiences are necessarily situated in his madness, in what way this madness is a condition for it and in what manner the Christian mystics to which Artaud refers (Eckhart, Rámon Llull, Teresa of Avila, John of the Cross or Swedenborg) help us to understand these experiences. Artaud’s mystical experiences are essentially embodied; they stem from the body and they are directed toward the body. The intense forces of life that traverse our body are tantamount, following Artaud, to what other mystics would have experienced and it is only by fortune that they have not been interned in a psychiatric hospital.